Chemical analysis and antimicrobial activity of Cumin seeds extracted oil against some bacterial and fungal isolates - Rafeef Amer Abdul Jabbar (University of Thi-Qar Journal of Science, 2019)
Cuminum cyminum seeds oil was extracted by using Soxhelt extraction ,the chemical analysis is carriedout by means of GC-MS ,1H-indene derivatives (59.77%) and Cuminic aldehyde(13.77%) are respectively themajor compound in the extracted oil . The Cumin oil exhibits a strong antibacterial activity against fourclinical bacterial isolates (Escherichia coli, Staphylococcus aureus, Klebsiella sp. and Pseudomonasaeruginosa) and strong to moderate antifungal activity against three fungal isolates (Aspergillus flavus,Candida albicans and Cryptococcus sp.). The minimum inhibitory concentration (MIC) of the Cuminextracted oil was applied against the clinical isolates of bacteria and E.coli was the most sensitive isolate, withthe lowest MIC value.